Biomarkers of Oxidative Stress in Huntington's Disease and Other Neurological Disorders: a Comparative Study - Marisol Peña Sánchez; Gabriel Andrés Peña de los Santos; Gretel Riverón Forment; Gloria Lara Fernández; Tatiana Acosta Sánchez; Alina González-Quevedo Monteagudo (Revista Finlay)
Foundation: biomarkers of oxidative stress in Huntington's disease could predict the course of the disease and evaluate new treatments, but their nonspecific nature seems to prevent the identification of any useful marker. Clarifying similarities and differences of this phenomenon and its behavior with clinical characteristics may be essential. Objective: compare biomarkers of oxidative stress between patients with Huntington's disease and other neurological disorders. Methods: an analytical, retrospective and case-control study was carried out (Huntington's disease, amyotrophic lateral sclerosis, spinocerebellar ataxia type 2 and ischemic stroke: acute and chronic stage). Demographic and clinical variables and markers of oxidative damage (malonildialdehyde, advanced protein oxidation products) and antioxidants (superoxide dismutase: catalase: glutathione peroxidase, plasma antioxidant capacity) were collected. Results: there were significant differences in malonyldialdehyde in Huntington's disease compared to the control (p=0.02), but not with the rest of the groups. The enzyme superoxide dismutase in Huntington's disease was statistically lower compared to amyotrophic lateral sclerosis, although for catalase it was higher in relation to the rest of the patients. FRAP in Huntington's disease was significantly lower versus amyotrophic lateral sclerosis and acute ischemic stroke. Advanced products of protein oxidation were directly correlated with the biological and onset ages of Huntington's disease. Motor activity in amyotrophic lateral sclerosis and neurological deficit in acute ischemic stroke were correlated with malonyldialdehyde and glutathione peroxidase, respectively. Conclusions: huntington's disease seems to show specific characteristics in its antioxidant system. Protein oxidation could be related to the accumulation of mutated huntingtin over time.